Therapeutic Effects of Cajuput Oil (Melaleuca Cajuputi) in Respiratory Health: A Systematic Review of Preclinical and Clinical Studies - Iwan Setiawan Adji; Faryn Dzaky; Annisa Naura; Shinta Aulia; Hanani Adeliya; Rheinasya Adisty (International Journal Of Health Science, 2026)
Respiratory tract diseases present significant challenges to global public health, requiring the development of multi-targeted, therapeutic interventions. Cajuput oil (Melaleuca cajuputi or Melaleuca leucadendra) and its primary monoterpene constituent, 1,8-cineole (eucalyptol), have demonstrated a broad spectrum of anti-inflammatory, antioxidant, spasmolytic, and antimicrobial properties. This systematic review synthesizes preclinical and clinical evidence to evaluate the therapeutic efficacy, underlying molecular mechanisms, clinical safety, and formulation advancements of cajuput oil and 1,8-cineole in managing upper and lower respiratory tract diseases. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, a systematic literature search was executed across PubMed, EuropePMC, and OpenAlex databases up to early 2026. Primary studies investigating the therapeutic effects of cajuput oil or 1,8-cineole in preclinical (in vitro and in vivo) and clinical respiratory disease models were selected. Six independent reviewers conducted the study screening, selection, data extraction, and risk of bias assessment. Result: Thirteen original studies met the rigorous eligibility criteria. In vivo animal models of pulmonary emphysema, pulmonary fibrosis, and allergic asthma showed that 1,8-cineole significantly attenuates tissue destruction, inflammatory cell infiltration, and fibrotic deposition. These cellular responses were mediated by the upregulation of Nrf2-driven antioxidant cascades and the suppression of NF-κB, p38 MAPK, and STAT6 inflammatory signaling pathways. Spasmolytic activities in human bronchial tissues were achieved via reversible H₁-receptor blockade and H₂-receptor/α-adrenoceptor activation. Furthermore, 1,8-cineole exhibited strong antimicrobial and antibiofilm properties against multidrug-resistant Klebsiella pneumoniae, Staphylococcus aureus, and Pseudomonas aeruginosa. In clinical trials and observational studies, oral administration of 1,8-cineole (including a novel amoxicillin-clavulanate-cineole formulation) significantly improved symptom severity and accelerated recovery in acute bronchitis, rhinosinusitis, and lower respiratory tract infections with excellent tolerability.